POTENSI MINYAK AKAR WANGI SEBAGAI KOSMETIKA.: POTENSI MINYAK AKAR WANGI SEBAGAI KOSMETIKA. - Muharam, Firman; Nurul, Nurul; Ekawati, Risrina Nur (Jurnal Medika Farmaka, 2024)
The cosmetics industry is experiencing rapid development with a variety of beauty products, and vetiver oil is emerging as a safe and effective natural ingredient with antioxidant, antimicrobial, and anti-aging benefits, and has the potential to overcome health problems caused by synthetic ingredients. Indonesia, as a major producer of vetiver oil, has a great opportunity to develop the market for natural cosmetics, increase the economic value of local agricultural products, and fulfil the global demand for environmentally-friendly natural cosmetics. Method: The article preparation method used literature reviews from international and national journals. The search for articles published online was conducted through PubMed and Google Scholar sites and citation writing using the Mendeley® software application. Result: Vetiver oil exhibits strong antioxidant and antimicrobial activities, able to protect cells from oxidative damage and is effective against various bacteria and fungi, with an IC50 of 0.515 µg for antioxidant activity and a Minimum Inhibitory Concentration (MWC) of 62.5 µg/ml against Bacillus cereus. In addition, the oil has anti-aging effects through increased lipid synthesis, aids in the treatment of acne by inhibiting the growth of Cutibacterium acnes, and reduces oxidative stress and melanin production, making it a potential agent in various skincare and health applications. Conclusion. Vetiver oil exhibits a range of significant health and beauty benefits, including antioxidant activity, antimicrobials, anti-aging effects, acne treatment, and oxidative stress reduction. Research and development of vetiver oil-based products can provide effective natural solutions to a wide range of health and cosmetic concerns.